Ethnic Diversity and Trust: New Evidence from Australian Data - Silvia Mendolia; Alex Tosh; Oleg Yerokhin (Institute for the Study of Labor (IZA), 2015)
This paper investigates the relationship between neighbourhood ethnic and linguistic heterogeneity and the formation of an individual's local and general trust. A wide literature across economics and sociology has recognised the importance of trust in facilitating economic growth and development and it is therefore important to investigate elements of social organisation that encourage or inhibit the development of trust. We use fixed effects and instrumental variable regression and control for a wide set of individual and local area characteristics to identify the effect of heterogeneity on trust formation. Our results show that increasing neighbourhood ethnic and linguistic fractionalisation is associated with a decrease in local trust of about 12% of a standard deviation in the model with fixed effects, while we do not find any significant relationship between neighbourhood heterogeneity and general trust.
Keywords: J15; Z10; 330; trust; social capital; ethnic fractionalization; ethnic heterogeneity; HILDA